AFL - CIO Songbook [bladmuziek]. - American Federation of Labor (AFL); Congress of Industrial Organizations (CIO) (Washington : AFL CIO)
Deze publicatie bevat volgende liederen
Star spangled banner
O Canada!
Red river valley
Down in the valley
Oh Suzanna
Auld lang syne
Home on the range
You are my sunshine
I've been working on the railroad
Clementine
Hand me down my walking cane
Let me call you sweetheart
On the top of old smoky
Silver threads among the gold
Wait till the sun shines, Nellie
Love's old sweet song
After the ball
When Irish eyes are ssssmiling
Daisy
Take me out to the ball game
Smiles
The sidewalks of New York
The band played on
My wild Irish Rose
I want a girl
Till we meet again
There's a long, long trail
Pack up your troubles
The mill was made of marble
Hallelujah, I'm a bum
Roll the union on
The soup song
Joe Hill
We will overcome
You gotta go down
The man that waters the workers' beer
Are you sleeping?
Goin' down the road
Casey Jones
We shall not be moved
Union Maid
Hnky Dinky parley vous
Which side are you on?
Too old to work
Hold the fort
It could be a wonderful world
When the new world is revealed
Great day
On the picket line
The give-away boys in Washington
Union Bonnet
All togheter
Mammy's little baby loves a union shop
Solidarity forever
Union Train
We are buiding a strong union
Engels
Partituur
Keywords: liederen